2006
DOI: 10.1111/j.1470-6431.2006.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Website evaluation criteria among US college student consumers with different shopping orientations and Internet channel usage

Abstract: The purpose of this study was to compare the website evaluation criteria among college student consumers in the US with different shopping orientations and Internet channel usage (i.e. online information searchers, online purchasers). The sample for this research was 414 college students, non‐married and aged 18–22 who have experience in visiting websites selling apparel products. Five apparel website evaluation criteria were identified by factor analysis (i.e. product information, customer service, privacy/se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
1
39
1
1
Order By: Relevance
“…However, it seems obvious that the research on website elements and/or the underlying online buying process can lead to improvements for online retailers. Seock and Chen-Yu (2007) identified five fashion website evaluation criteria -product information, customer service, privacy/ security, navigation, and auditory experience/comparison shopping -but as this approach only covers the time before and during the purchase itself, quality aspects of the fulfillment (e.g. the delivery time, returns handling) are not covered.…”
Section: Journal Of Global Fashion Marketing 195mentioning
confidence: 99%
“…However, it seems obvious that the research on website elements and/or the underlying online buying process can lead to improvements for online retailers. Seock and Chen-Yu (2007) identified five fashion website evaluation criteria -product information, customer service, privacy/ security, navigation, and auditory experience/comparison shopping -but as this approach only covers the time before and during the purchase itself, quality aspects of the fulfillment (e.g. the delivery time, returns handling) are not covered.…”
Section: Journal Of Global Fashion Marketing 195mentioning
confidence: 99%
“…Studies (Seock & Chen-Yu, 2007;Vrechopoulos, Siomkos & Doukindis, 2001) indicate an increasing number of Generation Y consumers exploring online shopping. Research has indicated that Generation Y consumers shop online for more products than the older age group (Sorce, Perroti & Widrick, 2005).…”
Section: Rationale For the Studymentioning
confidence: 99%
“…It is clear that the lack of easy access to payment systems is a huge barrier to young people as consumers in electronic shopping, with the recommendations from this study being to encourage e-retailers to adopt methods that allow parental access and control. Other studies that examine different relationships of adolescents or youths with e-shopping are Seock and Chen-Yu (2007), and Seock and Bailey (2008). Seock and Chen-Yu (2007) identify five online consumer shopping orientations for college students (aged 18-22) at two US universities, one in the East and one in the Mid-West.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that examine different relationships of adolescents or youths with e-shopping are Seock and Chen-Yu (2007), and Seock and Bailey (2008). Seock and Chen-Yu (2007) identify five online consumer shopping orientations for college students (aged 18-22) at two US universities, one in the East and one in the Mid-West. The authors focus on apparel websites because clothing constitutes one of the top categories of merchandise sold online, finding that, among the five criteria, privacy/security received the highest mean score in all situations for all purchaser groups.…”
Section: Introductionmentioning
confidence: 99%